Wyrd Questions: Re-framing Adult/ Community Education - Cheryl Hunt (Adult Education Research Conference, 2000)
There is a growing body of popular literature associated with ‘new paradigm’ research, the development of the Gaia hypothesis, and the meaning of ‘spirituality’ in today’s society. This paper suggests why adult/ community education should be re-framed within this context; and looks at some implications for model-building.